Pergeseran Terjemahan pada Teks Hadis dalam Dua Versi Terjemahan Kitab Tazkiyatun Nufus Wa Tarbiyatuha - Muhammad Yunus Anis; Hasna Nurul Istiqomah (Institut Agama Islam Negeri (IAIN) Metro, 2021)
This research analyses the translation shift of the hadis text in two versions of the translation of the tazkiyatun nufūs wa tarbiyatuhā works by Ibnu Rajab, Ibnu Qayyim and Imam Al-Ghazali, which Imtihan Asy-Syafi’i has translated as the first target text and which Umar Mujtahid has translated as the second target text. The translation shift in this study is divided into two. namely, shift in form and meaning. This translation shift occurred on the words. The purpose of this study is to describe the translation shift used by the translator in translating the tazkiyatun nufūs wa tarbiyatuhā book. The method used in this research is qualitative descriptive method. The source of the data in the form of book tazkiyatun nufūs wa tarbiyatuhā and two versions of its translation. The data analysis was done gradually. First, collecting the data and classify them according to the category. Second, presentsing the whole data the the translation shift in a coherent and includinge the answer for every formulation of the problem. Third, drawing conclusions based on the result of the study. The research showed that from 47 data, there are 2 types of shift in forms. Namely 35 data shift at the level of syntax, 6 data shift in word category. As for the shift in meaning, there are 2 types, namely 3 data shift of the meaning of the generic to the spesific and 3 data shift according to the cultural point of view.